Milho orgânico consorciado com adubos verdes: alternativas para o manejo de plantas daninhas - Balduino, Barbara Chrys Gomes (2020)
The cultivation of corn in an organic system is important to meet the production chains of milk, meat, and organic eggs. However, organic corn production faces two main challenges, weed management and mineral nutrition, especially nitrogen. The experiments were conducted in the 2017/18 and 2018/19 harvests in Araras (SP), in a randomized block design with four replications. In experiment 1 (Chapter 1) the treatments were corn intercropping with: Crotalaria spectabilis (5 plants m-1) (MC), Cajanus cajan (5 plants m-1) (MG) and Crotalaria spectabilis + Cajanus cajan (6 plants m-1, 3 plants of each green manure) (MCG) and one control, maize monoculture (M). Experiment 2 (Chapter 2) was installed in a 2x4 factorial scheme, two mechanical weed management methods, mowing and cultivator with hoes, and four corn intercropping with: Crotalaria spectabilis (5 plants m-1) (MC), Cajanus cajan (5 plants m-1) (MG) and Crotalaria spectabilis + Cajanus cajan (6 plants m-1, 3 plants of each green manure) (MCG) and one control, monoculture of corn (M). Weeds were evaluated in between the planting rows, in the stages of four and eight expanded leaves of corn. Wealth (S), Margalef diversity (α) and Shannon Index (H´) and Piellou equitability (E) of the community and the relative importance (IR) of weed species were determined. The data were also submitted to principal coordinate analysis (PCoA), along with the SIMPER multivariate analysis (similarity percentage). However, there was a reduction in species richness and diversity in the 2018/19 harvest. The consortia MG and MCG in the 2018/19 harvest presented weed composition closer to M and lower E, that is, predominance of fewer weeds. The cultivation systems had little influence on the IR of the main weeds. There was a predominance of summer weeds with late flowering and remaining in the off-season. The following were evaluated: corn growth: dry mass (MSM) and leaf area index (IAF) at stages V4, V8 (four and eight leaves) and VT (pendoamento) of corn. The dynamics of nitrogen: Falker chlorophyll index (ICF) in stages V4, V8 and VT, dry mass of green fertilizers (MSAV) in stages V8 and R6 (physiological maturation), nitrogen accumulation in MSAV at stage R6 and the content of N in corn kernels. The weed dry mass production (MSPD) in stages V8 and R6 and the productivity of corn grains. The mowing and the cultivator did not interfere in the MSM production. However, the grower favored the IAF increase. The largest MSAV productions occurred in the MC and MCG consortia. The lowest ICF for corn was in MG, indicating possible competition between corn and dwarf pigeon for nitrogen in the VT stage of corn. There was no difference between cultivation systems and weed management for N content and corn grain yield. The cultivator was not efficient for weed control in corn intercrops with green manures that produced higher MSAV.